Resolving Inconsistencies in Extreme Precipitation‐Temperature Sensitivities. Issue 18 (10th September 2020) - Visser, J. B.; Wasko, C.; Sharma, A.; Nathan, R.
Abstract: Extreme precipitation events are intensifying with increasing temperatures. However, observed extreme precipitation‐temperature sensitivities have been found to vary significantly across the globe. Here we show that negative sensitivities found in previous studies are the result of limited consideration of within‐day temperature variations due to precipitation. We find that short‐duration extreme precipitation can be better described by subdaily atmospheric conditions before the start of storm events, resulting in positive sensitivities with increased consistency with the Clausius‐Clapeyron relation across a wide range of climatic regions. Contrary to previous studies that advocate that dew point temperature drives precipitation, dry‐bulb temperature is found to be a sufficient descriptor of precipitation variability. We argue that analysis methods for estimating extreme precipitation‐temperature sensitivities should account for the strong and prolonged cooling effect of intense precipitation, as well as for the intermittent nature of precipitation. Plain Language Summary: Increasing global temperatures are likely to result in the intensification of extreme precipitation events with resultant flooding of great societal concern. Understanding the relationship between extreme precipitation and temperature provides valuable information for the design, operation, and risk assessment of high‐hazard infrastructure. However, the observed precipitation‐temperature relationship has been found to vary significantly across the globe, with negative relationships found in warmer climatic regions. Using station‐based subdaily observations, we show that careful sampling of higher temperatures measured before the start of the storm events can result in positive extreme precipitation‐temperature relationships across a wide range of climatic regions. Dry‐bulb temperature is found to drive short‐duration precipitation extremes, contradicting previous studies promoting dew point temperature as the main driver of precipitation variability. Our results indicate the use of coarser daily‐scale observations in previous studies contributed to obtaining negative relationships by limiting consideration for within‐day temperature variation caused by the rainfall event itself. Key Points: Correct sampling of dry‐bulb temperature before storm events resolves inconsistencies in extreme precipitation‐temperature sensitivities Previous underestimation of sensitivities is likely due to localized cooling and intermittent nature of precipitation Dry‐bulb temperature drives short‐duration precipitation extremes, contrary to previous dew point temperature based findings